Differences of Vitamin D Levels in Controlled and Uncontrolled Type 2 Diabetes Mellitus Patients - Adhisti Azlin; Ratna Akbari Ganie; Santi Syafril (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Vitamin D as an immunomodulator, plays an important role in controlling glycemic levels and decreasing diabetes complications. HbA1c is a marker of glycemic control which is known to have association with vitamin D. This study aims to see the differences in vitamin D serum levels and glycemic index in patients with type 2 DM.The design of this study is cross-sectional study and it was performed in RSUP HAM in December 2017 until March 2018. DM type 2 patients were classified based on HbA1c <7% controlled and â‰¥ 7% uncontrolled. Vitamin D serum levels were examined using the Enzyme-Linked Fluourescent Assay (ELFA) method., differences in vitamin D levels among controlled and uncontrolled type 2 diabetes mellitus were assessed by using independent t-test, and the differences of HbA1c level were assessed using Mann-Whitney-U test.45 patients with type 2 DM were divided into controlled (HbA1c <7%) and uncontrolled patients (HbA1c â‰¥ 7%). There was no difference in vitamin D serum levels between controlled and uncontrolled DM Type 2 patients (p = 0,310).